Calculation with MCNP of capture photon flux in VVER-1000 experimental reactor - Töre, Candan; Ortego, Pedro (Radiation protection dosimetry, 2005)
The aim of this study is to obtain by Monte Carlo method the high energy photon flux due to neutron capture in the internals and vessel layers of the experimental reactor LR-0 located in REZ, Czech Republic, and loaded with VVER-1000 fuel. The calclated neutron, photon and photon to neutron flux ratio are compared with experimental measurements performed with a multi-parameter stilbene detector. The results show clear underestimation of photon flux in downcomer and some overestimation at vessel surface and 1/4 thickness but a good fitting for deeper points in vessel.
Keywords: Models, Statistical; Radiation Protection; analýza selhání vybavení; počítačová simulace; Radiometry; Power Plants; Monte Carlo Method; statistické modely; fotony; Photons; Equipment Failure Analysis; radiometrie; Computer Simulation; metoda Monte Carlo; Czech Republic; radiační ochrana; Česká republika; elektrárny; radiační rozptyl; Radiation Dosage; dávka záření; Scattering, Radiation